Pedagogia da bricolagem: ofício de educadores e educadoras artífices - Cruz, Denise Santos da (2022)
This Thesis, developed in the Postgraduate Program in Education (PPGE), Federal University of Santa Maria (UFSM), research line “Teaching, knowledge and professional development”, presents the theme of a Pedagogy of Bricolàge as a craft of educators and artificer educators. Creative teaching is configured in pedagogical crafts - terms recommended by Sennett (2019, 2012) and Alliaud (2009; 2015; 2017; 2021a), in bio[trans]forming ambiences in school education. The theoretical-methodological plot has in Scientific Bricolage an emerging approach to research in education, based on Kincheloe (2006, 2007); Kincheloe; McLaren (2006); Neira; Lippi (2012). The corpus was inwrought in the interlocution with educators graduated from the PPGE and working in municipal public schools, bricolating academic memorials, reflective questions, portfolio, whose experiences and movements participate in the argumentative plot. The flow of Scientific Bricolage entered the field of research without apriorism, recognizing educators, male and female students and the pedagogical crafts they produced in bio(trans)forming ambiences. The experiences of continuous teacher and student learning give meaning to the processes of "weaving together the weft" and the craft of educating with pedagogical crafts, promoting multiple faces of a Pedagogy of Bricolage produced in the daily reinvented by artificer educators and students, in the brico-classes, dyeing here and there with colors and feelings.